Development of a colloidal gold immunochromatographic strip for the rapid detection of antibodies against Fasciola gigantica in buffalo - Wang, Jinhui; He, Kangxin; Wu, Zhengjiao; Jin, Weikun; Wu, Wende; Guo, Yanfeng; Zhang, Weiyu; Di, Wenda (Frontiers in Veterinary Science, 2022)
Background:  Fasciola gigantica, a tropical liver fluke, infects buffalo in Asian and African countries, causing significant economic losses and posing public health threats. The diagnostic of buffalo fascioliasis caused by F. gigantica is vital in fascioliasis control and preventation. The 22nd gel filtration chromatography fraction of F. gigantica Excretory-Secretory Products (FgESP), namely Fasciola 22 (F22), which was used as a diagnostic antigen in indirect ELISA, has demonstrated great potential for fascioliasis diagnosing. In the absence of rapid diagnostic methods, the use of a colloidal gold immunochromatographic strip based on F22 was applied to detect F. gigantica infection in buffalo. Methods: In the present study, the 22nd gel filtration chromatography fraction of FgESP (F22) was used as an antigen to establish the colloidal gold-based immunochromatographic strip (ICS). The nitrocellulose membrane was incubated with F22 at the test line (T line) and goat anti-mouse secondary antibody at the control line (C line). The mouse anti-buffalo secondary antibody 2G7 conjugated to colloidal gold particles was used as the detection system for line visualization. The strip was assembled and developed by optimizing reaction conditions and the sensitivity, specificity, stability, and early diagnostic value of the strip were evaluated. Results: An immunochromatographic strip for the rapid detection of antibodies against F. gigantica – FgICS – was developed. The strip demonstrated high sensitivity and specificity. Sensitivity tests confirmed positive results even when the positive reference serum was diluted 4,096 times. Except for one Schistosoma japonicum-positive serum that tested positive via FgICS, specificity tests confirmed no cross-reactivity with other positive sera of Schistosoma japonicum. The strip remained stable after storage at 4 °C for up to 3 months. In infected buffalo, antibodies could be detected as early as 14–21 days post-infection. The detection of 20 positive sera yielded an 85% positive rate via FgICS versus a 95% positive rate via ELISA based on FgESP. Conclusion: The immunochromatographic strip FgICS is rapid, simple, reliable, and suitable for use in detecting F. gigantica infection in the field.